PERANAN PROGRAM INVENTARISASI BAHAN BANGUNAN NASIONAL DALAM PEMBANGUNAN JALAN - Benny Moestofa (Direktorat Bina Teknik Jalan dan Jembatan, 1997)
Any highway engineering project requires information on the type, distribution, quality, reserve and cost of road-making materials. An inventory system to store this information for all Indonesia's provinces has been developed at Institute of Road Engineering (IRE). Indonesia, together with the collaboration of the Transport Research Laboratory (TRL) , United Kingdom. This article deals with the technical aspects of the inventory methodology which is applicable nationwide. The main benefit of this system is its use to road network planning and construction programmes in Indonesia. Although currently resricted tto road-making materials, the inventory system could be extended to cover other construction materials.